Analysis of the 3′UTR region of the NOTCH1 gene in chronic lymphocytic leukemia patients - Abramenko, I.V.; Bilous, N.I.; Chumak, A.A.; Dyagil, I.S.; Martina, Z.V. (Experimental Oncology, 2018)
Deregulation of NOTCH1-signalling pathway is common in chronic lymphocytic leukemia (CLL). The most of studies are focused on detection of the hotspot c.7541_7542delCT NOTCH1 mutations in exon 34, while studies of mutations in the 3′UTR region are rare. The aims of work were to evaluate the frequencies of mutations in the 3′UTR region of the NOTCH1 gene (9:136,495553-136,495994) in Ukrainian CLL patients, the distribution of rs3124591 genotypes located in that area, and association of NOTCH1 mutations with structure of B-cell receptor. Materials and Methods: Detection of mutations in the 3′UTR region of the NOTCH1 was performed by direct sequencing in 87 previously untreated CLL patients (from the total group of 237 CLL patients) with unmutated immunoglobulin heavy-chain variable (UM IGHV) genes and without mutations in hotspot regions of TP53, SF3B1, and exon 34 of NOTCH1 genes. Results: Mutations in the 3′UTR region of the NOTCH1 were revealed in three of 87 CLL patients (3.4%). Two cases with non-coding mutations were related to subset #1 of stereotyped B-cell receptors, and one case belonged to stereotyped subset #28a. Analysis with inclusion of 30 UM IGHV cases with previously detected c.7544_7545delCT mutations revealed that the frequency of UM IGHV genes of I phylogenetic clan (except IGHV1-69) was significantly increased, and the frequency of UM IGHV3 and IGHV4 genes, on the contrary, was reduced in NOTCH1-mutated cases comparing with NOTCH1-unmutated cases (p = 0.002) and the general group (p = 0.013). SNP rs3124591 did not affect the risk of CLL and survival parameters of the patients. At the same time, differences were found in the frequency of IGHV gene usage and in the structure of HCDR3 in carriers of individual genotypes. Conclusion: The frequency of NOTCH1 mutations in 3′UTR region was low. Our findings confirmed current data on the association between the structure of the B-cell receptor and the appearance of NOTCH1 mutations. Some features of HCDR3 structure were identified in carriers of TT and CC genotypes of rs3124591. Key Words: NOTCH1 mutations, 3′UTR region of the NOTCH1, rs3124591, IGHV genes.